PC.39 Reliability of Myocardial Performance Assessment in Preterm Infants using Strain and Strain Rate: A comparison Between Left ventricular, Septal and Right ventricular Walls. (9th June 2014) - James, A; Corcoran, D; Jain, A; Mertins, L; McNamara, P; Franklin, O; El-Khuffash, A
Abstract : Objective: To assess the reliability of longitudinal strain (LS) and strain rate (SR) in the very low birth weight infants. Design/Methods: LS and SR were measured in infants less than 28 weeks corrected gestational age using colour tissue Doppler at the mid segment of the LV free wall, the intra-ventricular septum and RV free wall from the apical 4-chamber view. Intra and inter-observer reliability was assessed using intra class correlation coefficient (ICC) and Bland-Altman Analysis. Results: 48 infants with a mean (SD) gestation and birth weight of 26.9(1.3) weeks and 959(230) grams underwent an echocardiogram at 11(5) hours of life. The RV and septal walls demonstrated superior bias and agreement when compared to the LV free wall. Conclusions: Assessment of LS and SR in preterm infants using colour tissue Doppler is feasible with the RV and septal wall providing better reliability results. Further study of those parameters in preterm disease states is warranted.